2012
DOI: 10.1038/eye.2012.122
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-wide-field autofluorescence imaging in non-traumatic rhegmatogenous retinal detachment

Abstract: Purpose Rhegmatogenous retinal detachment (RRD) affects the function of the retina before and after surgical repair. We investigated ultra-wide-field autofluorescence (UAF) abnormalities in patients with acute RRD to improve our understanding of the functional changes in the retina before and after surgery. Methods In this retrospective study, we present the UAF imaging findings of 16 patients with acute, non-traumatic RRD. Imaging was obtained with the Optos 200 Tx (Optos) in 14 eyes preoperatively and in 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 14 publications
(13 reference statements)
1
46
1
Order By: Relevance
“…Compared to indirect ophthalmoscopy, UWF imaging can, in some cases, provide a more precise documentation of the extent of the detachment [38]. The UWF FAF provides prognostic information and a means for examining the postoperative functional status of the previously detached retina [37,39]. Witmer et al [37] reported that patients with macula-involving detachments who showed persistent postoperative granular autofluorescent changes had significantly worse preoperative visual acuity and showed a trend toward worse postoperative visual prognosis.…”
Section: Retinal Detachmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared to indirect ophthalmoscopy, UWF imaging can, in some cases, provide a more precise documentation of the extent of the detachment [38]. The UWF FAF provides prognostic information and a means for examining the postoperative functional status of the previously detached retina [37,39]. Witmer et al [37] reported that patients with macula-involving detachments who showed persistent postoperative granular autofluorescent changes had significantly worse preoperative visual acuity and showed a trend toward worse postoperative visual prognosis.…”
Section: Retinal Detachmentmentioning
confidence: 99%
“…The UWF FAF provides prognostic information and a means for examining the postoperative functional status of the previously detached retina [37,39]. Witmer et al [37] reported that patients with macula-involving detachments who showed persistent postoperative granular autofluorescent changes had significantly worse preoperative visual acuity and showed a trend toward worse postoperative visual prognosis. Labriola et al [40] reported on a case in which UWF and UWF FA were helpful in documenting neovascularization and macrocyst formation associated with chronic retinal detachment (Fig.…”
Section: Retinal Detachmentmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the use of filters allows ultrawidefield autofluorescence and angiographic imaging [48,50]. Ultrawidefield autofluorescence imaging may be of particular use for detection of degenerative changes of the peripheral retina in patients with AMD [51].…”
Section: Ultrawidefield Imagingmentioning
confidence: 99%
“…8,9 This imaging modality, known as "ultra-widefield," has been used in the adult patient population to evaluate and manage various retinal diseases, including diabetic retinopathy, choroidal lesions, uveitis, retinal vascular occlusion, retinal detachment, and sickle cell retinopathy. 6,7,[10][11][12][13][14][15][16][17][18][19][20][21] However, the feasibility and utility of this imaging modality have not been well characterized in the pediatric patient population. In this case series, we demonstrate the utility of using ultra-widefield digital fundus photography and ultra-widefield fluorescein angiography (UWFA) in the pediatric patient population to evaluate peripheral retinal pathology and to assist in the management and treatment of Coats' disease and FEVR.…”
Section: Introductionmentioning
confidence: 99%